(untitled) (Construction Economics and Building, 2010)
Residential mortgage products (also known as home loans) pricing has been long understood to be something of a ‘dark art’, requiring judgment and experience, rather than being an exact science. In the last decade, a lot has changed in this field and more and more lenders, primarily the larger lenders, are increasingly looking to make their pricing as exact as possible. Even so, inadequate pricing of residential mortgage products (in particular its substandard risk pricing) has been seen as one of major causes of the global financial crisis (GFC) and subsequent spectacular banking collapses. The underlying theme of the paper is to exhibit how contemporary lenders, in practice, price their residential mortgage products. While discussing elements of the pricing calculation particular attention was given to the exposition of how contemporary lenders price risks involved in providing home loans. Because of the importance of Basel capital accords to how financial institutions assess and quantify their risks, the paper provides an overview of Basel capital accords. The author envisages that the paper will (i) help enhance comprehension of the underlying elements of the pricing calculation and the ways in which these elements relate to each other, (ii) scrutinize how contemporary lenders identify and quantify risks and (iii) improve consciousness of future changes in interest rates